Biological properties and surgical applications of the human amniotic membrane - Munoz-Torres, Jose R.; Martínez-González, Sidney B.; Lozano-Luján, Alan D.; Martínez-Vázquez, María C.; Velasco-Elizondo, Perla; Garza-Veloz, Idalia; Martinez-Fierro, Margarita L. (Frontiers in Bioengineering and Biotechnology, 2023)
The amniotic membrane (AM) is the inner part of the placenta. It has been used therapeutically for the last century. The biological proprieties of AM include immunomodulatory, anti-scarring, anti-microbial, pro or anti-angiogenic (surface dependent), and tissue growth promotion. Because of these, AM is a functional tissue for the treatment of different pathologies. The AM is today part of the treatment for various conditions such as wounds, ulcers, burns, adhesions, and skin injury, among others, with surgical resolution. This review focuses on the current surgical areas, including gynecology, plastic surgery, gastrointestinal, traumatology, neurosurgery, and ophthalmology, among others, that use AM as a therapeutic option to increase the success rate of surgical procedures. Currently there are articles describing the mechanisms of action of AM, some therapeutic implications and the use in surgeries of specific surgical areas, this prevents knowing the therapeutic response of AM when used in surgeries of different organs or tissues. Therefore, we described the use of AM in various surgical specialties along with the mechanisms of action, helping to improve the understanding of the therapeutic targets and achieving an adequate perspective of the surgical utility of AM with a particular emphasis on regenerative medicine.